The identity of Buchanania yunnanensis, as a new synonym of Spondias pinnata (Anacardiaceae) - Le, Chi-Toan; Lin, Qin-Wen; Tan, Yun-Hong; Zhu, Ren-Bin; Hao, Yun-Qing; Liu, Bing (Phytotaxa, 2021)
Buchanania yunnanensis was published based on a specimen consisting of a flowering branch without any leaves or fruits. Examination of morphological characters based on type specimens and our newly collected materials has shown that B. yunnanensis was incorrectly placed in Buchanania. At the time of description, and indicates that it is actually conspecific with Spondias pinnata. It is here reduced to a synonym of the latter species.